Formulation and Evaluation of Ketoconazole Nano-suspension - Agustin, Eriska; Sari, Gita Deslia (Journal of Food and Pharmaceutical Sciences, 2024)
The use of antifungals that are widely used by the public is ketoconazole. Ketoconazole is included in the Biopharmaceutical Classification System (BCS) II category, where the drug is poorly soluble in water but has high permeability. In this study, ketoconazole was prepared in a nanosuspension formulato increase solubility. The method for preparing 2% ketoconazole nanosuspension used a sonicator bath with variations of tween 80 (F1 8%, F2 10%, F3 12%) and transcutol as surfactant and co-surfactant. The results showed that the particle size of the ketoconazole nanosuspension F1 was 102 ± 4.3 nm, F2 was 105 ± 3.2 nm, and F3 was 90 ± 2.4 nm on day 0. Testing on day 28 showed an increase in particle size in F1 115 ± 3.1 nm, F2 129±4.5nm, F3 97±2.4nm (p>0.05). In testing the morphology of the nanosuspension using Scanning Electron Microscopy (SEM), The results showed that the irregular spheres were scattered. Organoleptic testing showed clear and homogeneous preparations. pH testing for 28 days showed a pH range of 5.6-6 which is included in the physiological skin pH range (p>0.50). Nanosuspension preparations can be said to meet the physical evaluation requirements.